PROMOTING PRO-ENVIRONMENTAL BEHAVIOR THROUGH DISASTER EDUCATION - Julian Amriwijaya; Tutty I. Sodjakusumah (Adisam Publisher, 2025)
Disaster education has a strategic role in encouraging pro-environmental behavior by increasing public awareness of the relationship between human activities, disasters, and environmental sustainability. This study discusses various strategies for implementing disaster education, including integration into the formal curriculum, strengthening extracurricular programs, community involvement, utilization of technology, and policy support. With a comprehensive approach, disaster education can be an effective tool in forming a society that is more prepared for disasters and more environmentally conscious. Support from various stakeholders, such as the government, educational institutions, non-governmental organizations, and the private sector, is essential to ensure the sustainability of this program. Evaluation and monitoring are also important factors in increasing the effectiveness of disaster education. In conclusion, disaster education is not only a mitigation tool but also a strategy in building pro-environmental awareness and behavior for the sustainability of the ecosystem and the welfare of future generations.